Block architecture influence on the structure and mechanical performance of drawn polyurethane elastomers. Issue 7 (7th January 2014) - Fernández‐d'Arlas, Borja; Corcuera, Marian; Runt, James; Eceiza, Arantxa
<x xml:space="preserve">Abstract</x> The macromolecular orientation of some polyurethane elastomers can led to materials with varied mechanical properties. These properties are dependant on the molecular structure of both hard and soft segmants. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>